Penerapan Arsip Elektronik di Kantor Perpustakaan, Arsip, dan Dokumentasi Kota Bukittinggi - Yunita Yunita; Elva Rahmah (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
Writing this article aims to describe (1) the implementation of electronic filing in the Office of Libraries, Archives and Documentation Bukittinggi; (2) obstacles in the implementation of electronic filing in the Office of Libraries, Archives and Documentation Bukittinggi; (3) efforts should be made so that the implementation of an electronic archive goes well at the Office of Libraries, Archives and Documentation of Bukittinggi. Data collected by observation and interviews with archivists and the study of literature in the implementation of electronic filing in the Office of Libraries, Archives and Documentation of Bukittinggi. Data analysis was done descriptive. Based on the discussion, it can be concluded that (1) the activities in the implementation of electronic filing in the Office of Libraries, Archives and Documentation Bukittinggi starting scan archived data, data entry, edit data, and publication of archives; (2) there are still obstacles encountered in the Application of Electronic Records in the Office of Libraries, Archives and Documentation Bukittinggi; (3) the efforts made by the Office of Libraries, Archives and Documentation Bukittinggi namely: improving infrastructure, enhancing human resources by means of training and education and broaden through the media. Keywords: Implementation, electronic archives